ANALISIS PENERAPAN AKUNTANSI PERTANGGUNGJAWABAN SEBAGAI ALAT PENGENDALIAN BIAYA DI RUMAH SAKIT HERMANA LEMBEAN - Doda, Isabella; Manossoh , Hendrik; Maradesa, Djeini (GOING CONCERN : JURNAL RISET AKUNTANSI, 2023)
One of the control tools used by management in controlling costs and revenues is the accountability accounting system. The more optimal the implementation of accountability accounting in the company, the more effective the cost control. The object of this study was the Hermana Lembean hospital. This study aims to find out and obtain a clear picture of accountability accounting applied as a cost control tool at Hermana Lembean hospital. The type of data in this study is qualitative data. The data sources used are primary data sources, and secondary data sources. The results of this study show that Hermana hospital has implemented accountability accounting quite well and accountability accounting as a cost control tool at Hermana Lembean hospital is not yet sufficient. Overall the difference that occurs shows a favorable deviation, but there are some costs that show a considerable difference in adverse deviation.